On Polynomial Solutions of Pell’s Equation - Hasan Sankari; Ahmad Abdo (Journal of Mathematics)
Polynomial Pell’s equation is x2−Dy2=±1, where D is a quadratic polynomial with integer coefficients and the solutions X,Y must be quadratic polynomials with integer coefficients. Let D=a2x2+a1x+a0 be a polynomial in Zx. In this paper, some quadratic polynomial solutions are given for the equation x2−Dy2=±1 which are significant from computational point of view.